Chlorpropamide alcohol flush and circulating met-enkephalin: a positive link. - Medbak, S (1981)
Chlorpropamide-alcohol flushing may be due to sensitivity to endogenous opiates. To investigate this possibility the plasma met-enkephalin and beta-endorphin responses to sherry with and without chlorpropamide were studied in six patients with non-insulin dependent diabetes and in six normal subjects. After chlorpropamide all patients showed a rise in met-enkephalin concentrations from a basal level of 50 +/- 7.2 ng/l to a peak of 75 +/- 8.1 ng/l (p less than 0.001). In contrast, before chlorpropamide treatment was started met-enkephalin values did not change after alcohol. No significant changes in beta-endorphin values were observed. In six normal subjects pretreated with chlorpropamide the met-enkephalin concentration also rose from a basal level of 72 +/- 15 ng/l to a peak of 103 +/- 9.4 ng/l (p less than 0.002). Again, the met-enkephalin rise was not observed after placebo. Neither beta-endorphin concentrations nor facial temperature changed significantly. These data suggest that endogenous opiates may be implicated in CPAF. Furthermore, this is the first study in which a significant change in circulating met-enkephalin values has occurred.